2020
DOI: 10.3389/fnagi.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Effect of Transcranial Alternating Current Stimulation on Motor Skill Consolidation

Abstract: Transcranial alternating current stimulation (tACS) is the application of subthreshold, sinusoidal current to modulate ongoing brain rhythms related to sensory, motor and cognitive processes. Electrophysiological studies suggested that the effect of tACS applied at an alpha frequency (8-12 Hz) was state-dependent. The effects of tACS, that is, an increase in parieto-occipital electroencephalography (EEG) alpha power and magnetoencephalography (MEG) phase coherence, was only observed when the eyes were open (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…In addition, entrainment of other cortical regions, especially left IPL, which is tightly connected to right cerebellum (Bostan et al, 2013), as well as the observed coherence between PMC and cerebellum suggests that tACS targeting the cerebellum could entrain local oscillatory activity. Surprisingly, 10Hz tACS to left M1 did not significantly affect learning compared to sham as expected from previous work (Fresnoza et al, 2020;Pollok et al, 2015). In previous studies, stimulation electrodes were placed over left M1 (at C3 or lM1 measured by TMS) and right orbita possibly leading to a distributed effect over not just M1 but PMC and large portions of prefrontal areas (e.g.…”
Section: Limitationssupporting
confidence: 58%
See 1 more Smart Citation
“…In addition, entrainment of other cortical regions, especially left IPL, which is tightly connected to right cerebellum (Bostan et al, 2013), as well as the observed coherence between PMC and cerebellum suggests that tACS targeting the cerebellum could entrain local oscillatory activity. Surprisingly, 10Hz tACS to left M1 did not significantly affect learning compared to sham as expected from previous work (Fresnoza et al, 2020;Pollok et al, 2015). In previous studies, stimulation electrodes were placed over left M1 (at C3 or lM1 measured by TMS) and right orbita possibly leading to a distributed effect over not just M1 but PMC and large portions of prefrontal areas (e.g.…”
Section: Limitationssupporting
confidence: 58%
“…In motor sequence learning, 10Hz tACS to left primary motor cortex (M1) led to enhanced performance in some studies (Antal et al, 2008;Pollok et al, 2015) but disrupted consolidation in others (Rumpf et al, 2019) with conflicting effects depending on age (Fresnoza et al, 2020). Importantly these studies could not establish a link between learning and actual oscillatory entrainment in the α range.…”
Section: Introductionmentioning
confidence: 89%
“…Individual alpha-peak (IAF) tACS improved older adults' implicit motor learning performance and alpha-tACS at IAF + 2 Hz improved performance in younger and older adults. On the contrary, online gamma-tACS slowed reaction times, while online theta-tACS had no effect on implicit motor learning [62,63,66]. Gamma-tACS increased motor sequence learning, while alpha-and beta-tACS had no effect [65,67].…”
Section: Discussionmentioning
confidence: 89%
“…Fresnoza and colleagues [63] applied tACS at the IAF or IAF + 2 Hz. Following the application of tACS, younger and older participants completed an implicit motor learning task.…”
Section: Procedural Memory (Motor Learning)mentioning
confidence: 99%
“…In contrast to tACS research, it seems that NFB research has investigated more types of factors, which may influence brain responsiveness to NFB. Within tACS research, factors, such as aging (Fresnoza et al, 2020 ), actual health condition (Krause et al, 2014 ), baseline (pre-stimulation) level of the targeted EEG activity (Neuling et al, 2013 ; Alagapan et al, 2016 ; Ruhnau et al, 2016 ; Bächinger et al, 2017 ; Lefebvre et al, 2017 ; Berger et al, 2018 ), placebo (Antal and Herrmann, 2016 ), ceiling effect (Krause et al, 2014 ; Fresnoza et al, 2020 ), a specific type of cognitive activity during which tACS is induced (Feurra et al, 2013 ), and illumination condition (Kanai et al, 2008 , 2010 ; Stecher et al, 2017 ), have been examined. In NFB research, several factors related to brain state have been investigated, including baseline level of the target EEG activity (Travis et al, 1974 ; Wan et al, 2014 ; Nicholson et al, 2016 ; Nan et al, 2020 ), the level of illumination of the treatment room (Paskewitz and Orne, 1973 ; Cram et al, 1977 ), ceiling effect (Hardt and Kamiya, 1978 ), placebo (Mullinix et al, 1978 ; Plotkin and Rice, 1981 ; Holroyd et al, 1984 ; Kotchoubey et al, 2001 ; Thibault and Raz, 2017 ; Shibata et al, 2019 ), aging (Staufenbiel et al, 2014 ), the brain morphology (Enriquez-Geppert et al, 2013 ), healthy brain vs. pathological condition (Ros et al, 2017a ), the effect of fatigue (Choobforoushzadeh et al, 2015 ), the effect of anxiety (Hardt and Kamiya, 1978 ; Kadosh and Staunton, 2019 ), the effect of mental strategies used for enhancing NFB-rewarded neural activity (Lacroix and Roberts, 1978 ; Sepulveda et al, 2016 ; Lubianiker et al, 2019 ; Shibata et al, 2019 ), the effects of mood (Kadosh and Staunton, 2019 ), and the personality traits (Ancoli and Kamiya, 1978 ; Peciuliene et al, 2015 ).…”
Section: Factors Influencing Responsiveness To Tacs and Nfbmentioning
confidence: 99%